The Landbouwschool and the Impact for Indo-European Society in Giesting, Lampung, 1926-1942 - Rinaldo Adi Pratama; Syahna Ardani; Yusuf Perdana; Muhammad Adi Saputra; Nainunis Aulia Izza (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2025)
Abstract: In the early 20th century, Indo-Europeans in the Dutch East Indies faced increasing socio-economic marginalization, driven by competition with indigenous populations and limited access to land and labor opportunities. In response, the Indische Europese Vereniging (I.E.V.) initiated colonization efforts beyond Java, notably in the Lampung region, where a settlement named Giesting was established. This study examines the role of education in developing the Giesting colony, focusing on the founding of the Landbouwschool (Agricultural School) in 1929 as a key institution in cultivating agrarian skills and community identity among Indo-Europeans. Using a historical methodology comprising heuristics, source criticism, interpretation, and historiography, this research draws on archival documents, oral histories, and secondary literature to trace the socio-cultural and economic functions of the school. The findings reveal that the Landbouwschool served as a center for agricultural training and a mechanism of social integration and empowerment for a community in a precarious colonial position. The institution's legacy persists in the local toponymy and memory, offering insights into the intersection of education, identity, and colonial settlement policy in the late Dutch East Indies. This study contributes to broader discussions on colonial education, race, and social engineering in comparative imperial contexts. Abstrak: Pada awal abad ke-20, Masyarakat Indo-Eropa di Hindia Belanda menghadapi marjinalisasi sosial ekonomi akibat meningkatnya persaingan dengan penduduk pribumi serta keterbatasan akses terhadap tanah dan kesempatan kerja. Sebagai respons, Indische Europese Vereniging (I.E.V.) memprakarsai upaya kolonisasi di luar Pulau Jawa, khususnya di wilayah Lampung, yang kemudian dikenal dengan nama Giesting. Penelitian ini mengkaji peran pendidikan dalam perkembangan koloni Giesting, dengan menitikberatkan pada pendirian Landbouwschool (Sekolah Pertanian) pada tahun 1929 sebagai institusi kunci dalam pembentukan keterampilan agraris dan identitas komunitas Indo-Eropa. Menggunakan metode penelitian sejarah yang mencakup heuristik, kritik sumber, interpretasi, dan historiografi, penelitian ini memanfaatkan dokumen arsip, sejarah lisan, dan literatur sekunder untuk menelusuri fungsi sosial, kultural, dan ekonomi dari sekolah tersebut. Temuan menunjukkan bahwa Landbouwschool tidak hanya berperan sebagai pusat pelatihan pertanian, tetapi juga sebagai alat integrasi sosial dan pemberdayaan bagi komunitas yang menempati posisi kolonial yang ambigu. Dampak dari sekolah ini masih dapat ditelusuri melalui toponimi lokal dan ingatan kolektif masyarakat, serta memberikan wawasan mengenai hubungan antara pendidikan, identitas, dan kebijakan pemukiman kolonial pada masa akhir pemerintahan Hindia Belanda. Studi ini memberikan kontribusi terhadap diskusi yang lebih luas mengenai pendidikan kolonial, ras, dan rekayasa sosial dalam konteks imperialisme.